Role of auxin during intercellular infection of Discaria trinervis by Frankia - Imanishi, Leandro; Perrine-Walker, Francine M.; Ndour, Adama; Vayssières, Alice; Conejero, Genevieve; Lucas, Mikaël; Champion, Antony; Laplaze, Laurent; Wall, Luis; Svistoonoff, Sergio (Frontiers in Plant Science, 2014)
Nitrogen-fixing nodules induced by Frankia in the actinorhizal plant Discaria trinervis result from a primitive intercellular root invasion pathway that does not involve root hair deformation and infection threads. Here, we analyzed the role of auxin in this intercellular infection pathway at the molecular level and compared it with our previous work in the intracellular infected actinorhizal plant Casuarina glauca. Immunolocalisation experiments showed that auxin accumulated in Frankia-infected cells in both systems. We then characterized the expression of auxin transporters in D. trinervis nodules. No activation of the heterologous CgAUX1 promoter was detected in infected cells in D. trinervis. These results were confirmed with the endogenous D. trinervis gene, DtAUX1. However, DtAUX1 was expressed in the nodule meristem. Consistently, transgenic D. trinervis plants containing the auxin response marker DR5:VENUS showed expression of the reporter gene in the meristem. Immunolocalisation experiments using an antibody against the auxin efflux carrier PIN1, revealed the presence of this transporter in the plasma membrane of infected cells. Finally, we used in silico cellular models to analyse auxin fluxes in D. trinervis nodules. Our results point to the existence of divergent roles of auxin in intercellularly- and intracellularly-infected actinorhizal plants, an ancestral infection pathways leading to root nodule symbioses.